Commercialisation of university patents: A case study - Ismail, Kamariah; Cooper, Sarah; Abdul Majid, Izaidin; Mason, Colin; Wan Omar, Wan Zaidi (2009)
The role of universities has evolved over time. The most recent manifestation is the ‘Entrepreneurial University’, which engages with industry through various knowledge transfer programs, and seeks to commercialise its research output. One of the consequences is increases in patenting of university research output. However, both the number and proportion of exploited patents is small. The primary aim of this paper is to explain why some patents are exploited, through, spin-off formations and/or through licensing to established companies, while others are not. This involved exploring the factors and actors in the patenting and commercialising patents in a university in Scotland, to understand the different outcomes. In total, 22 patents from a portfolio of 82 were studied. The study employed qualitative methods incorporating a case study approach. Two samples of patents from the University patents portfolio, one comprising patents that were commercially exploited, and the other comprising unexploited patents, were examined. Exploited patents were those that were licensed to established companies, and those that were used to start new spin-off companies. This study was then supplemented with interviews with the TTO director at the University and six other university TTO Directors. The study finds that, whether a patent is commercially exploited, and the way in which it is exploited is influenced by three main factors: (i) the entrepreneurs and the inventors, their characteristics and motivations; (ii) the characteristics and nature of the technologies; and (iii) the TTO’s resources and lack of a due diligence system. The study finally suggests proposals for how TTOs can enhance their decision-making process, regarding which discoveries to patent in order to improve the overall effectiveness of commercialisation process in universities. Key words: Commercialisation process, academic entrepreneur, spin-off formation, licensing to established companies, exploited patents, unexploited patents